The Fortifications of the Late Scythian Settlement at Konsulivske - Marcin Matera; Nadiya Gavrylyuk (Archaeologia Polona)
Konsulivske belongs to the group of Late Scythian hillforts located in the lower Dnipro area. Since 2015, a Ukrainian–Polish archaeological team has been carrying out the investigation of the site. The article presents the results of these studies focused on fortifications of the citadel and the main line of defence.